Angklung as a Tool for Diplomacy and Cross-Cultural Communication - Buky Wibawa Karya Guna; Diah Fatma Sjoraida (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Angklung is a traditional musical instrument inherited from Indonesia. This study uses a literature study method that is relevant to the research objectives. The results of the research show that angklung is a world heritage. Apart from that, angklung is a traditional art tool that was originally part of a ritual ceremony and then continues to develop and adapt to changing times to become a functional art for entertainment. Angklung is a form of non-material culture that has the potential to be a source of local history that has values that can be passed on to future generations. Angklung was created from the diversity of ethnic groups, customs, and cultures. The existence of angklung has been recognized by UNESCO as Indonesia's official world cultural heritage, this UNESCO recognition extends the list of Indonesian cultural heritage that is recognized by the world. Angklung is one of the country's abilities to invite other countries to cooperate. Angklung can increasingly become a cross-cultural communication because it develops in other countries. Angklung has a long history and has existed since ancient times until now. Angklung is not used as pure art, but as art that functions in religious activities.